Structure and Temporal Change of the Credit Network between Banks and Large Firms in Japan - Hiroshi Iyetomi; Yuichi Ikeda; Hideaki Aoyama; Yoshi Fujiwara; Wataru Souma (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
We present a new approach to understanding credit relationships between commercial banks and quoted firms, and with this approach, examine the temporal change in the structure of the Japanese credit network from 1980 to 2005. At each year, the credit network is regarded as a weighted bipartite graph where edges correspond to the relationships and weights refer to the amounts of loans. Reduction in the supply of credit affects firms as debtor, and failure of a firm influences banks as creditor. To quantify the dependency and influence between banks and firms, we propose a set of scores of banks and firms, which can be calculated by solving an eigenvalue problem determined by the weight of the credit network. We found that a few largest eigenvalues and corresponding eigenvectors are significant by using a null hypothesis of random bipartite graphs, and that the scores can quantitatively describe the stability or fragility of the credit network during the 25 years.
Keywords: E52; G21; E51; 330; Banking; credit topology; bipartite network; systemic risk; Kredit; Bank; Lieferanten-Kunden-Beziehung; Business Network; Graphentheorie; Japan